Theology As a Way of Life: On Teaching and Learning the Christian Faith - Neder, Adam (Baker Academic, 2019)
This clear and creative theological and spiritual reflection on the art of teaching the Christian faith provides a wealth of fresh insights for anyone involved in teaching and learning Christianity.